The Systematic Elusiveness of God: On the Fiftieth Anniversary of Ian Ramsey's Religious Language - Tilley, Terrence W. (Horizons, 2007)
Ian Ramsey (1915-1972) had a significant impact on analytical philosophy of religion in the second half of the twentieth century. This article claims that one of his early articles, "The Systematic Elusiveness of ‘I’," and the passing comments on Thomas Aquinas in his most famous work, Religious Language (1957), are keys to understanding his contributions. Though his work is out of vogue with many philosophers of religion today, he anticipated a number of significant developments in philosophy and his work remains used by and useful for systematic theologians.